2018
DOI: 10.1136/bmjopen-2017-019661
|View full text |Cite
|
Sign up to set email alerts
|

Association of chronic kidney disease with mortality risk in patients with lung cancer: a nationwide Taiwan population-based cohort study

Abstract: ObjectiveOur population-based research aimed to clarify the association between chronic kidney disease (CKD) and mortality risk in patients with lung cancer.DesignRetrospective cohort studySettingNational health insurance research database in TaiwanParticipantsAll (n=1 37 077) Taiwanese residents who were diagnosed with lung cancer between 1997 and 2012 were identified. Eligible patients with baseline CKD (n=2269) were matched with controls (1:4, n=9076) without renal disease according to age, sex and the inde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 16 publications
(14 reference statements)
0
21
0
Order By: Relevance
“…In a recent population‐based cohort study in Taiwan of lung cancer patients with coexisting CKD, Wei et al . found that CKD increased the mortality risk by 38% . The authors used specific International Classification of Disease codes to determine CKD and included mostly CKD stage 5 patients .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In a recent population‐based cohort study in Taiwan of lung cancer patients with coexisting CKD, Wei et al . found that CKD increased the mortality risk by 38% . The authors used specific International Classification of Disease codes to determine CKD and included mostly CKD stage 5 patients .…”
Section: Discussionmentioning
confidence: 99%
“…8 In a recent population-based cohort study in Taiwan of lung cancer patients with coexisting CKD, Wei et al found that CKD increased the mortality risk by 38%. 7 The authors used specific International Classification of Disease codes to determine CKD and included mostly CKD stage 5 patients. 7 In this study, the CKD-CG showed a 4% decrease in survival in lung cancer patients with CKD (HR 0.96, 95% 0.88-1.08; P = 0.65) while the CKD-EPI showed a 5% increased risk of death (HR 1.05, 95% CI 0.95-1.17; P = 0.33) ( Table 5).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Using the NHIRD, Wang’s work surveyed second primary malignancy risk after radiotherapy for patients with rectal cancer [13]. Researchers used the NHIRD to prove that the survival of lung cancer is affected by a common comorbidity, chronic renal insufficiency [14]. A type of Chinese herb was demonstrated to improve the survival of lung cancer with this database [15].…”
Section: Introductionmentioning
confidence: 99%